Burns in the elderly: a nationwide study on management and clinical outcomes - Goei, Harold (Burns Trauma, 2020)
BACKGROUND: In modern-day burn care, advanced age remains an important predictor for mortality among burn victims. In this study, we compared the complete treatment trajectory (including pre-hospital and surgical treatment) and the outcomes between an elderly burn population and a younger adult burn population. METHODS: In this nationwide study, data from the Dutch Burn Repository were used. This is a uniform national registration for Dutch specialized burn care. All adult patients that were admitted to one of the three Dutch burn centres from the period 2009 to 2015 were included in the analysis. Burn patients were considered as elderly when ≥65 years of age, and were then further subdivided into three age categories: 65–74, 75–85 and 85+ years. Younger adults in the age category 18–64 years were used as the reference group. Surgical management was studied comprehensively and included timing of surgery, the number of procedures and details on the surgical technique, especially the technique used for debridement and the grafting technique that was applied. For the comparison of clinical outcome, the following parameters were included: mortality, wound infections, length of stay/TBSA (total body surface area) burned, discharge disposition and secondary reconstructions. RESULTS: During the study period, 3155 adult patients were included (elderly, n = 505). Burn severity, reflected by the median TBSA, varied between 3.2–4.0% and was comparable, but aetiology and pre-hospital care were different between elderly and the younger adult reference group. Surgical treatment was initiated significantly faster in elderly burn patients (p < 0.001). Less selective techniques for surgical debridement were used in the elderly burns patients (hydrosurgery, 42.0% vs 23.5–22.6%), and on the other hand more avulsion (5.3% vs 7.3–17.6%) and primary wound closure (6.7% vs 24.5%). The most frequently used grafting technique was meshed skin grafts (79.2–88.6%); this was not related to age. Mortality increased rapidly with a higher age and showed a high peak in the 85+ category (23.8%). Furthermore, considerable differences were found in hospital discharge disposition between the elderly and the reference group. CONCLUSIONS: In conclusion, elderly burn patients who require specialized burn care are vulnerable and medically challenging. Differences in aetiology, comorbidity, physiology and the management prior to admission possibly affect the initial surgical management and result in significantly worse outcomes in elderly. Elderly patients need optimal, timely and specialized burn care to enhance survival after burn injuries.